LEGAL PROTECTION OF CONSUMERS REGARDING ILLEGAL ONLINE COSMETIC DISTRIBUTION IS REVIEWED FROM LAW NO. 8 OF 1999 CONCERNING CONSUMER PROTECTION - Auchia Indah; Aryuda Aryuda (Riviera Publishing, 2024)
The writing of this scientific paper entitled